2014
DOI: 10.1016/j.jue.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol availability and crime: Lessons from liberalized weekend sales restrictions

Abstract: In February 2000, the Swedish state monopoly alcohol retail company launched a large scale experiment in which all stores in selected counties were allowed to keep open on Saturdays. We assess the effects on crime of this expansion in access to alcohol. To isolate the impact of the experiment from other factors, we compare conviction rates in age cohorts above and below the national drinking age restriction in counties where the experiment had been implemented, and contrast these differences to those in counti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…There is an extensive literature on the relationship between alcohol availability and crime. 5 For example, researchers have studied the effects of alcohol taxes (Cook and Moore, 1993;Markowitz, 2000Markowitz, , 2001Markowitz, , 2005Markowitz and Grossman, 2000;DeSimone, 2001;Cook and Piette Durrance, 2013), Federal Prohibition (Miron, 1999;Owens, 2011), the minimum legal drinking age (Joksch and Jones, 1993;Carpenter, 2005;Carpenter and Dobkin, 2015), underage drunk driving laws (Carpenter, 2005(Carpenter, , 2007, restrictions on weekend sales (Heaton, 2012;Gr€ onqvist and Niknami, 2014) and early closing times for bars and restaurants (Chikritzhs and Stockwell, 2002;Hough and Hunter, 2008;Biderman et al, 2010;De Mello et al, 2013). 6 A separate strand of this literature has focused on the spatial relationship between establishments that sell alcohol and crime.…”
Section: Alcohol Consumption and Crimementioning
confidence: 99%
“…There is an extensive literature on the relationship between alcohol availability and crime. 5 For example, researchers have studied the effects of alcohol taxes (Cook and Moore, 1993;Markowitz, 2000Markowitz, , 2001Markowitz, , 2005Markowitz and Grossman, 2000;DeSimone, 2001;Cook and Piette Durrance, 2013), Federal Prohibition (Miron, 1999;Owens, 2011), the minimum legal drinking age (Joksch and Jones, 1993;Carpenter, 2005;Carpenter and Dobkin, 2015), underage drunk driving laws (Carpenter, 2005(Carpenter, , 2007, restrictions on weekend sales (Heaton, 2012;Gr€ onqvist and Niknami, 2014) and early closing times for bars and restaurants (Chikritzhs and Stockwell, 2002;Hough and Hunter, 2008;Biderman et al, 2010;De Mello et al, 2013). 6 A separate strand of this literature has focused on the spatial relationship between establishments that sell alcohol and crime.…”
Section: Alcohol Consumption and Crimementioning
confidence: 99%
“…They found that each one-hour extension of closing hours was associated with a statistically significant increase of 4.8 assaults. Grönqvist and Niknami (2014) studied a natural experiment during the introduction of Saturday openings of Swedish alcohol retail stores in several counties in 2000.…”
Section: Impacts By Alcohol-related Harmmentioning
confidence: 99%
“…A significant 18.7% raise in Saturday crime among male youths was found when alcohol outlets in six selected counties (hosted 3 800 000 inhabitants/almost half of the total Swedish population) were allowed to keep open on Saturdays in Sweden 29. This increase was confined to crimes committed on Saturdays and was driven by illegal activity among individuals with low compulsory schooling grades and among person with fathers that have completed at least some secondary education.…”
Section: Resultsmentioning
confidence: 99%